1+tan theta the whole square + 1+cot theta the whole square = sec theta+ cosec theta the whole square
Answers
Step-by-step explanation:
Given---->
( 1 + tanθ )² + ( 1 + Cotθ )² = ( Secθ + Cosecθ )²
Proof ----> LHS
= ( 1 + tanθ )² + ( 1 + Cotθ )²
we know that ,
( a + b )² = a² + b² + 2ab , applying it we get,
= 1 + tan²θ + 2tanθ + 1 + Cot²θ + 2Cotθ
= ( 1 + tan²θ ) + ( 1 + Cot²θ ) + 2tanθ + 2Cotθ
We know that,
1 + tan²θ = Sec²θ
1 + Cot²θ = Cosec²θ
applying these formulee , we get,
= Sec²θ + Cosec²θ + 2 ( tanθ + Cotθ )
We know that,
tanθ = Sinθ / Cosθ , Cotθ = Cosθ / Sinθ , applying it we get,
= Sec²θ + Cosec²θ + 2(Sinθ / Cosθ + Cosθ / Sinθ)
= Sec²θ + Cosec²θ + 2 (Sin²θ + Cos²θ/Sinθ Cosθ)
We know that,
Sin²θ + Cos²θ = 1 , applying it we get,
= Sec²θ + Cosec²θ + 2 ( 1 / Sinθ Cosθ )
= Sec²θ + Cosec²θ + 2 ( 1 / Sinθ ) ( 1 / Cosθ )
We know that,
Cosecθ = 1 / Sinθ , Secθ = 1 / Cosθ , applying it we get,
= Sec²θ + Cosec²θ + 2 Cosecθ Secθ
= ( Secθ )² + ( Cosecθ )² + 2 ( Cosecθ ) ( Secθ )
= ( Secθ + Cosecθ )²
Answer:
so hard question I don't know answer of this question